Los Myxomycetes citados de México - Ogata, Nisao; Nestel, David; Rico-Gray, Victor; Guzman, Gaston (Instituto de Ecología, A.C., 1994)
A list of the species and varieties of Myxomycetes reported as occurring in Mexico is presented. The list is based on 34 references published between 1892-1992 and yields a total of 187 species and two varieties, which represent 37.4% of the world’s taxa. The majority of these studies are inventories, a few are taxonomic studies and only one is an ecological study. No Myxomycetes are recorded from the states of Aguascalientes, Baja California Sur, and Sinaloa. The states of Veracruz, Nuevo Leon, Chiapas, Quintana Roo, Guerrero, Mexico, and Yucatan have, respectively, the highest number of species. Widely distributed species in the country are: Ceratiomyxa fruticulosa, Hemitrichia calyculata and Cribraria violacea. The myxomycetes of the tropical zone, despite their being poorly collected, represent 49% of the species known from México, indicating the potential richness of those ecosystems.